Mechanochemical solid state synthesis of copper(I)/NHC complexes with K3PO4 - Remy-Speckmann, Ina; Zimmermann, Birte M.; Gorai, Mahadeb; Lerch, Martin; Teichert, Johannes F. (Beilstein Journal of Organic Chemistry, 2023)
A protocol for the mechanochemical synthesis of copper(I)/N-heterocyclic carbene complexes using cheap and readily available K3PO4 as base has been developed. This method employing a ball mill is amenable to typical simple copper(I)/NHC complexes but also to a sophisticated copper(I)/N-heterocyclic carbene complex bearing a guanidine moiety. In this way, the present approach circumvents commonly employed silver(I) complexes which are associated with significant and undesired waste formation and the excessive use of solvents. The resulting bifunctional catalyst has been shown to be active in a variety of reduction/hydrogenation transformations employing dihydrogen as terminal reducing agent.
Keywords: ball mill; bifunctional catalysis; catalytic hydrogenations; copper; mechanochemical synthesis; N-heterocyclic carbenes